Ancient DNA Evidence from China Reveals the Expansion of Pacific Dogs. (8th January 2020) - Zhang, Ming; Sun, Guoping; Ren, Lele; Yuan, Haibing; Dong, Guanghui; Zhang, Lizhao; Liu, Feng; Cao, Peng; Ko, Albert Min-Shan; Yang, Melinda A; Hu, Songmei; Wang, Guo-Dong; et al.
Abstract: The ancestral homeland of Australian dingoes and Pacific dogs is proposed to be in South China. However, the location and timing of their dispersal and relationship to dog domestication is unclear. Here, we sequenced 7, 000- to 2, 000-year-old complete mitochondrial DNA (mtDNA) genomes of 27 ancient canids (one gray wolf and 26 domestic dogs) from the Yellow River and Yangtze River basins (YYRB). These are the first complete ancient mtDNA of Chinese dogs from the cradle of early Chinese civilization. We found that most ancient dogs (18/26) belong to the haplogroup A1b lineage that is found in high frequency in present-day Australian dingoes and precolonial Pacific Island dogs but low frequency in present-day China. Particularly, a 7, 000-year-old dog from the Tianluoshan site in Zhejiang province possesses a haplotype basal to the entire haplogroup A1b lineage. We propose that A1b lineage dogs were once widely distributed in the YYRB area. Following their dispersal to South China, and then into Southeast Asia, New Guinea and remote Oceania, they were largely replaced by dogs belonging to other lineages in the last 2, 000 years in present-day China, especially North China.